Acrobatic training prevents learning impairments and astrocyte remodeling in the hippocampus of rats undergoing chronic cerebral hypoperfusion: sex-specific benefits - Martini, Ana Paula Rodrigues; Schlemmer, Livia Machado; Lucio Padilha, Joelma Alves; Fabres, Rafael Bandeira; Couto Pereira, Natividade de Sá; Pereira, Lenir Orlandi; Dalmaz, Carla; Netto, Carlos Alexandre (Frontiers in Rehabilitation Sciences, 2024)
BackgroundChronic cerebral hypoperfusion (CCH) leads to memory and learning impairments associated with degeneration and gliosis in the hippocampus. Treatment with physical exercise carries different therapeutic benefits for each sex. We investigated the effects of acrobatic training on astrocyte remodeling in the CA1 and CA3 subfields of the hippocampus and spatial memory impairment in male and female rats at different stages of the two-vessel occlusion (2VO) model.MethodsWistar rats were randomly allocated into four groups of males and females: 2VO acrobatic, 2VO sedentary, sham acrobatic, and sham sedentary. The acrobatic training was performed for 4 weeks prior to the 2VO procedure. Brain samples were collected for morphological and biochemical analysis at 3 and 7 days after 2VO. The dorsal hippocampi were removed and prepared for Western blot quantification of Akt, p-Akt, COX IV, cleaved caspase-3, PARP, and GFAP. GFAP immunofluorescence was performed on slices of the hippocampus to count astrocytes and apply the Sholl's circle technique. The Morris water maze was run after 45 days of 2VO.ResultsAcutely, the trained female rats showed increased PARP expression, and the 2VO-trained rats of both sexes presented increased GFAP levels in Western blot. Training, mainly in males, induced an increase in the number of astrocytes in the CA1 subfield. The 2VO rats presented branched astrocytes, while acrobatic training prevented branching. However, the 2VO-induced spatial memory impairment was partially prevented by the acrobatic training.ConclusionAcrobatic training restricted the astrocytic remodeling caused by 2VO in the CA1 and CA3 subfields of the hippocampus. The improvement in spatial memory was associated with more organized glial scarring in the trained rats and better cell viability observed in females.